Synthesis and Characterization of Ferric Oxide-Graphite-Activated Carbon Composites - Adhikari, Mandira Pradhananga; Humagain, Nabin; Budhathoki, Biplab (Journal of Nepal Chemical Society, 2025)
Activated carbon-based composite electrodes have been widely utilized to enhance the specific capacitance of electrodes. In this study, the effect of the amount of activated carbon on Fe₂O₃-graphite (FGs) was investigated. Fe₂O₃ nanoparticles incorporated with graphite were synthesized using a co-precipitation method. The composites were characterized using X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), and UV-Vis spectrophotometry. The FTIR spectra revealed sharp peaks, indicating the successful incorporation of graphite into all four Fe₂O₃ nanoparticle samples in their pure state after calcination. XRD analysis showed that the Fe₂O₃/graphite nano-powders had uniform particle sizes when calcined at 400 °C, with an average crystallite size of approximately 30 nm. The Fe₂O₃-graphite-activated carbon composite prepared with varying amounts of activated carbons (FG-0.25, FG-0.33, FG-0.5, and FG-1.0), was analyzed for its electrochemical performance via cyclic voltammetry (CV). The FG-1.0 composite, with a higher activated carbon content, exhibited a remarkably high capacitance of 1372 F g⁻¹. This significant improvement could be attributed to the dual role of activated carbon as a highly conductive support material and as a provider of an enlarged surface area, which enhances charge transfer efficiency. These findings suggest the potential of Fe₂O₃-graphite-activated carbon composites for large-scale power generation applications.